The influence of perceived threat on the motive attribution asymmetry bias for groups in conflict - Rebecca E. Hughes; Brandon D. Stewart (PLoS ONE, 2025)
Previous research shows higher perceived threat is related to more intergroup bias, usually via greater ingroup positivity. Newer research has identified the Motive Asymmetry Attribution Bias in which ingroup and outgroup members make very different explanations for the motives about why their groups are in conflict. We were interested in this Motive Asymmetry Bias and its relationship to perceived threat with groups in conflict, so we designed two studies to investigate it cross-sectionally (Study 1) and longitudinally (Study 2). We recruited samples of American Republicans and Democrats to complete an online survey measuring perceived threat and Motive Asymmetry Bias. Regression analyses indicated that perceived threat was not related to ratings of one’s own party; however, higher perceived threat was related to more negative ratings of the other party. This discovery is important to help inform different ways to intervene to improve intergroup relations, especially for groups in conflict.